การทำความเย็นแบบดูดซึม (Absorption Refrigeration) - ชิยางคบุตร, สุรศักดิ์ (Engineering and Applied Science Research, 2013)
The continuous type and the intermittent type of absorption refrigeration’s were described. Heat used in operating the cycle is from several sources such as steam, flue gas, solar energy etc.